Investment Strategy In The Capital Market - Haryanti, Eka (Journal of Accounting and Management, 2024)
The purpose of this research is to determine the role of the capital market in investment in Indonesia's economic growth. The capital market is a financial market for long-term funds.This article explains the benefits of capital market instruments, risks and strategies in the capital market. Investment can be done in various ways, one of which is by utilizing the capital market. The capital market carries out two functions at once, namely an economic function and a financial function. In the capital market, there are several instruments of concern, namely shares, rights and bonds. Apart from capital market instruments, when investing in the capital market you must be aware of the types of risks such as purchasing power risk, business risk, interest rate risk, market risk and liquidity risk. Understanding several types of risk in the capital market will make it possible to create strategies, for example collecting several types of shares in one portfolio, buying on the primary market and selling once they are listed on the stock exchange, buying and holding, buying sleeping shares, stock switching strategies, consulting on certain industries, and mutual funds.